Cross-Cultural Christian Education in the Metaverse: Developing Virtual Faith Communities for Global Spiritual Formation and Interfaith Dialogue - Oktavianus Rangga (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This study aims to explore the role of cross-cultural Christian education in cyberspace in supporting the formation of virtual faith communities for global spiritual formation and interfaith dialogue. Issues that include the challenges of globalization and digitalization that change the way communities interact, especially in religious contexts. The methods used are concept analysis and literature studies that support the development of a theoretical framework for digital-based cross-cultural education. The results of the study indicate that digital platforms can be an effective means of creating inclusive cross-cultural dialogue spaces, strengthening spiritual identity, and facilitating cross-cultural learning. The findings also highlight the importance of design programs that are sensitive to cultural and technical contexts. The main conclusion of this study is that cross-cultural Christian education in cyberspace can be a powerful tool for advancing global solidarity and interfaith dialogue. However, its success depends on collaboration between educators, technology developers, and religious communities, as well as attention to obstacles such as digital literacy and unequal access to technology.